Total knee arthroplasty: indication of blood transfusion according to hematimetric variation and clinical symptoms of hypoperfusion, - Rodrigo Tavares Cardozo; Edison Fidelis de Souza Junior; Wagner Campoli Alves; Flávio Barbi Filho (Revista Brasileira de Ortopedia, 2014)
Objective:To analyze the relationship between hematimetric variation and the presence of clinical symptoms of hypoperfusion for indicating blood transfusion in patients undergoing total knee arthroplasty.Methods:A retrospective analysis was conducted on data gathered from the medical files of 55 patients with a diagnosis of gonarthrosis, who underwent total knee arthroplasty at a hospital orthopedics and traumatology service between February 2011 and December 2012. The patients studied presented unilateral joint degeneration and fitted into the indications for surgical treatment. All the patients underwent a preoperative cardiological evaluation, presenting a pattern of ASA I–III and absence of blood dyscrasia, and preoperative hemoglobin measurements were made. However, no minimum hematimetric value was established for the surgical treatment; there were only clinical criteria for blood perfusion.Results:Among the 55 patients, 35 were female and 20 were male, and the mean age was 68 years. Six patients underwent homologous blood transfusion, because of their clinical condition of tissue hypoperfusion, persistent hypotension, loss of consciousness, sweating and coercible vomiting. They presented postoperative hemoglobin of 7.5–8.8 g/dL.Conclusion:For patients with falls in hemoglobin counts greater than 20% and values lower than 9 g/dL after the surgery, there is a possible need for blood transfusion, which should only be indicated when accompanied by major symptoms of tissue hypoperfusion.